EVALUATION OF THE ADIWIYATA SCHOOL PROGRAM IN AN EFFORT TO DEVELOP A PANCASILA STUDENT PROFILE STRENGTHENING PROJECT - Fatmawati Hiola; Tita Rosita; Sendi Ramdhani (Pena Cendekia Insani, 2025)
This study aims to analyze the influence of Word of Mouth, Direct Marketing, and Digital Marketing on Brand Awareness through Event Marketing as a mediating variable. The research employs a quantitative approach with survey methods involving 505 respondents. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that all paths in the model are statistically significant. Word of Mouth, Direct Marketing, and Digital Marketing each have a significant direct effect on Event Marketing and Brand Awareness. Moreover, Event Marketing significantly mediates the relationship between the three independent variables and Brand Awareness. These results highlight the importance of integrating communication strategies to effectively build brand awareness through interactive and experiential channels.